Sustainable integration of artificial intelligence and machine learning approaches within the African infectious disease vaccine research and development ecosystem - Hare, Jonathan; Nielsen, Morten; Kiragga, Agnes; Ochiel, Daniel (Frontiers in Pharmacology, 2024)
Artificial Intelligence and Machine Learning (AI/ML) techniques, including reverse vaccinology and predictive models, have already been applied for developing vaccine candidates for COVID-19, HIV, and Hepatitis, streamlining the vaccine development lifecycle from discovery to deployment. The application of AI and ML technologies for improving heath interventions, including drug discovery and clinical development, are expanding across Africa, particularly in South Africa, Kenya, and Nigeria. Further Initiatives are required however to expand AI/ML capabilities across the continent to significantly impact African vaccine and drug development including developing the requisite knowledge base, fostering collaboration between stakeholders, ensuring robust regulatory and ethical frameworks and investment in infrastructure that are essential for building a sustainable ecosystem.